Proceedings of the Thirteenth ACM Symposium on Operating Systems Principles 1991
DOI: 10.1145/121132.121164
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of a distributed file system

Abstract: We analyzed the user-level file access patterns and caching behavior of the Sprite distributed file system. The first part of our analysis repeated a study done in 1985 of the BSD UNIX file system. We found that file throughput has increased by a factor of 20 to an average of 8 Kbytes per second per active user over 10-minute intervals, and that the use of process migration for load sharing increased burst rates by another factor of six. Also, many more very large (multi-megabyte) files are in use today than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(48 citation statements)
references
References 10 publications
1
46
0
Order By: Relevance
“…We used two different types of real workload traces: file system traces from the Sprite network file system [18] and database traces that consist of the DB2 trace used by Johnson and Shasha [10] and the OLTP trace used by both O'Neil et al [11] and Johnson and Shasha [10].…”
Section: Resultsmentioning
confidence: 99%
“…We used two different types of real workload traces: file system traces from the Sprite network file system [18] and database traces that consist of the DB2 trace used by Johnson and Shasha [10] and the OLTP trace used by both O'Neil et al [11] and Johnson and Shasha [10].…”
Section: Resultsmentioning
confidence: 99%
“…These have a negative impact on cache performance, as they can effectively stream through and flush the cache for large enough files, if action is not taken to mitigate such behaviour. Baker et al report cache read miss rates of about 40% in their study, rising to 97% on machines processing large files [12].…”
Section: Cachingmentioning
confidence: 88%
“…Vogels [200] found that files are open for even shorter periods: 75% are open for less than 10 milliseconds, and 55% of new files are deleted within 5 seconds; 26% are overwritten within 4 milliseconds. Similarly, both Baker et al [12] and Vogels [200] confirm that most files accessed are short, and sequentially accessed (but shifting more towards random access), but that most bytes transferred belong to large files, and that large files are getting larger (20% are 4 MB or larger).…”
Section: Workload Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…Simulated models are fed with the Sprite File System trace data from the University of California at Berkeley Baker, Hartman, et al 1991 . These traces are publically available.…”
Section: Remote Memory Variable-size Client Cachesmentioning
confidence: 99%